Analisis tingkat penerapan materi diklat terhadap kinerja alumni diklat fasilitasi Alat dan Mesin Pertanian (ALSINTAN) pasca panen - Murdani Murdani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2019)
This research was conducted to find out the level of implementation of training materials, tools and agricultural machinery post-harvest facilitation on the performance of agricultural extension. This research was used descriptive quantitative approach, analysis data that was done using descriptively, verification and regresion methods. Descriptive method was used to describe the implementation of the training, the level of support/ facilitation the training results that related with the job description/function, and to know the supporting factors and obstacles in applying the training results related with job description/function of the alumni of the training. Verification method was used to know the corelation or causality between variables (support from supervisors, facilities from the leader, cross-confirmation, support from colleagues/partners) are evaluated by data analysis techniques (correlation) using SPSS. Correlation for verification the material application results obtained by data from direct supervisors, colleagues/partners and the assisted farmers. While the regression method was used to determine the effect of facilities from the leader, the intensity of accompaniment to the farmers and evaluation of accompaniment on the level of implementation the materials. The results showed that the average level of material implementation to the training material is 50% of the total material trained based on the statement of the direct supervisors, colleagues/partners and the assisted farmers. The result of correlation between the participants origins and the level of material application shows that the highest level of material application came from West Nusa Tenggara and Central Java Provinces, while the improvement of performance with the implementation of the lowest training materials came from Bali and East Nusa Tenggara Provinces. The training material implementation level was 9% influenced by the facilities from direct supervisor, the intensity of accompaniment, evaluation of accompaniment and level of implementationby farmers.